2012
DOI: 10.1111/j.1745-4530.2012.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

A KINETIC APPROACH TO SAPONIN EXTRACTION DURING WASHING OF QUINOA (CHENOPODIUM QUINOA WILLD.) SEEDS

Abstract: The aim of this work was to show that the leaching process of saponins from quinoa (Chenopodium quinoa Willd.) seeds during washing with water, as is generally practiced by people in South America, can be modeled using mathematical expressions related to Fick's second law. Experimental data were obtained through batch extraction with a ratio of quinoa to water of 1:10 under constant agitation for processing time between 15 and 120 min at 20, 30, 40, 50 and 60C. It was found that residual saponin concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
6
22
0
2
Order By: Relevance
“…The reason was that these compounds could not be extracted successfully – possibly due to the presence of polar ‘sapogenins’ or other ‘unknown’ compounds interfering the extraction. A recent study has shown that aqueous extraction is not particularly efficient for removing saponins from quinoa seeds and a removal of only 32% was reported . In the present work, the amount of saponins were, however, low in all hydrolysates (data not shown).…”
Section: Resultsmentioning
confidence: 80%
“…The reason was that these compounds could not be extracted successfully – possibly due to the presence of polar ‘sapogenins’ or other ‘unknown’ compounds interfering the extraction. A recent study has shown that aqueous extraction is not particularly efficient for removing saponins from quinoa seeds and a removal of only 32% was reported . In the present work, the amount of saponins were, however, low in all hydrolysates (data not shown).…”
Section: Resultsmentioning
confidence: 80%
“…Determination of total saponins (TS) content was carried out based on a modified reversed‐phase HPLC procedure described by Quispe‐Fuentes et al . For it, an HPLC device (Agilent 1200 Series HPLC system, Santa Clara, CA, USA) including a diode array detector (DAD) set at 210 nm and an automatic injector was employed.…”
Section: Methodsmentioning
confidence: 99%
“…The data from kinetic studies are needed to design the production equipment such as reactor or extractor. Moreover, the kinetic model also improves the procedure precision, minimizing processing errors and increasing the final quality of the product [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies of extraction kinetics for saponin from Sapindus rarak DC. To our best knowledge, few studies have explained the saponin extraction kinetics, such as kinetic studies of saponin leaching from quinoa seed [12,16] and kinetic studies of saponin extraction from Saponaria vaccaria L. seeds [17]. The previous kinetic studies were focused on the leaching mechanism to obtain saponin, where the raw materials were only soaked for a specific time in a solvent.…”
Section: Introductionmentioning
confidence: 99%